Analisis Perencanaan Strategis Sistem Informasi Pada Manies Group Madiun dengan Pemodelan Ward And Peppard Untuk Meningkatkan Pelayanan Pelanggan - Anardani, Sri; Putera, Andi Rahman (Universitas Diponegoro, 2018)
Manies Group is a company engaged in the sale of fashion that has been known by the people of the City of Madiun since 1971. Business competition is getting higher with the construction of several Mall and Department Stores. One strategy to deal with such competition is through information technology and information systems. For this reason, it is necessary to analyze the information system strategic planning for Manies Group. The purpose of this study is to identify data needs to develop information systems and information technology. The planning analysis methodology uses the framework of John Ward and Joe Peppard. The analysis results are mapped using portfolio designs using McFarlan's Strategic Grid. The final result of this research is a document on the IS / IT strategic plan that supports the process of designing and building information systems for Manies Group